On the Boundary Value Problem with the Operator in Boundary Conditions for the Operator-Differential Equation of Second Order with Discontinuous Coeficients - Mirzoev, S.S.; Aliev, A.R.; Rustamova, L.A. (Журнал математической физики, анализа, геометрии, 2013)
Suficient conditions for regular solvability of the boundary value problem for an elliptic operator-differential equation of second order considered on the positive semi-axis are obtained. Note that the principal part of the equation contains a discontinuous coefficient, and the boundary condition involves a linear operator. Найдены достаточные условия регулярной разрешимости краевой задачи для эллиптического операторно-дифференциального уравнения второго порядка, рассматриваемого на положительной полуоси. Отмечено, что главная часть уравнения содержит разрывной коэффициент, а в краевом условии участвует линейный оператор.